Mindfulness-Based stress reduction in early palliative care for people with metastatic cancer: A mixed-method study. (December 2019) - Poletti, Stefano; Razzini, Giorgia; Ferrari, Roberto; Ricchieri, Maria Pia; Spedicato, Giorgio Alfredo; Pasqualini, Antonella; Buzzega, Cristina; Artioli, Fabrizio; Petropulacos, Kyriakoula; Luppi, Mario; Bandieri, Elena
Highlights: Participants' accounts show a personal, spiritual reconnection throughout the intervention. The interplay between the group dynamics and individual mindfulness exercises led participants to reframe their condition. The abilities, learned during the intervention, allowed participants to develop a sort of existential gratitude. Focusing on breathing, an accepting attitude towards pain or difficult emotions, such as panic and anguish, is developed. Abstract: Objectives: To explore the impact of a Mindfulness-Based Stress Reduction (MBSR) intervention for people with metastatic cancer integrated in Early Palliative Care (EPC). Design: Mixed-method study. Settings/Location: EPC Service integrated with Oncology Unit, Carpi General Hospital, Italy from January to October 2017. The MBSR intervention took place inside the hospital. Subjects: Study participation was offered to 25 consecutive people referred to the EPC service. Inclusion criteria: people with metastatic cancer between 18 and 75 years old; informed consent. Exclusion criteria: Performance Status <60% according to Karnofsky scale; active psychiatric disorder. 20 patients were included in the study. Intervention: The adapted program consists of 8 meetings for 2.5 h once a week, a 4.5 h session between the 6th and 7th weeks and 0.5 h home practice daily. The following mindfulness practices were included during the training: formal sitting meditation, body scan, light yoga, walking meditation, and Aikido exercises. Participants were provided with materials for home practice. A qualified MBSR instructor conducted the program. Sessions were attended by a clinical psychologist and a physician trained in meditation, together with the palliative nurse as facilitators. Outcome Measures: Feasibility and acceptability were assessed on 16 participants. In addition, pre-post measures of cancer pain and mood state were collected. Semi-structured, in-depth interviews were conducted on a subset of 8 participants at the end of the study and analysed using the Interpretative-Phenomenological approach. Results: MBSR attendance to meetings and adherence to home practice were 75%. MBSR intervention helped participants to develop an accepting attitude in respect to metastatic cancer disease helping them to face anxiety and cancer pain. MBSR improves self-regulation of mood state engendering feelings of compassion MBSR program supports participants in questioning and reconnecting with their values and spiritual beliefs. Conclusions: A Mindfulness intervention integrated into EPC setting is feasible, well accepted and could help metastatic cancer patients to control cancer pain together with an opportunity of emotional and spiritual relief.